HP-DF SSK Method for UAVs Communication in Cooperative Multi-Hop Rician Networks - Tastan, Mustafa Cihan; Ilhan, Haci (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
This paper presents techniques that are expected to improve the bit error rate (BER) performance of Unmanned Aerial Vehicles (UAVs) communication systems. The decode-and-forward (DF)-based cooperative multi-hop Rician network using space shift keying (SSK) modulation is employed for this purpose. The SSK modulation and cooperative communication are merged and used together. This enhances the BER performance for multiple-input multiple-output (MIMO) channels, thus accentuating its significance as an important technique for consistently reliable communication methodology while, at the same time, eliminating wastage of energy. The new technique is named as high performance (HP) due to not only BER performance improvement but also increase of the diversity of the communication system. This new model is further used for multi-hop networks and the resulting BER characteristics are assessed for possible enhanced performance in Rician channels. The paper also showcases the generalized-n-hop BER equation for various multi-hop DF-based cooperative communication systems in diverse UAV models. The Monte Carlo simulations further confirm the theoretical results that already exist for transmit-receive antennas. This work also underlines the fact that the number of hops in a communication system has no bearing whatsoever on the BER performance diversity value.
Keywords: Rician channels; Spread spectrum communication; Modulation; Cooperative communication; Bit error rate; Transmitting antennas; Receiving antennas; Air-to-air (A2A); bit error rate (BER); decode-and-forward (DF); ground-to-air (G2A); high performance (HP); multiple-input-multiple-output (MIMO) systems; space shift keying (SSK) modulation; unmanned aerial vehicles (UAVs); AERIAL VEHICLES UAVS; CIVIL APPLICATIONS; MIMO; INTERNET; MODEL; Engineering; Telecommunications; Transportation